2019
DOI: 10.1002/cncr.31999
|View full text |Cite
|
Sign up to set email alerts
|

Hyperprogressive disease in early‐phase immunotherapy trials: Clinical predictors and association with immune‐related toxicities

Abstract: BackgroundA subset of patients treated with immune checkpoint inhibitors experience an accelerated tumor growth rate (TGR) in comparison with pretreatment kinetics; this is known as hyperprogression. This study assessed the relation between hyperprogressive disease (HPD) and treatment‐related toxicity and clinical factors.MethodsThis study reviewed patients with solid tumors who were enrolled in early‐phase immunotherapy trials at Princess Margaret Cancer Centre between August 2012 and September 2016 and had c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
142
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 125 publications
(149 citation statements)
references
References 22 publications
3
142
4
Order By: Relevance
“…The phenomenon of enhanced progression after checkpoint blockade has been described with different checkpoint blockade agents and in numerous tumor types including, but not limited to, non‐small cell lung, head and neck, breast, gastric, and genitourinary cancers . The fact that various histologies that can be afflicted by HPD suggests that there could be common, histology‐agnostic biologic or molecular mechanism(s).…”
Section: Criteria For and Predictors Of Hpd According To Different Rementioning
confidence: 99%
See 2 more Smart Citations
“…The phenomenon of enhanced progression after checkpoint blockade has been described with different checkpoint blockade agents and in numerous tumor types including, but not limited to, non‐small cell lung, head and neck, breast, gastric, and genitourinary cancers . The fact that various histologies that can be afflicted by HPD suggests that there could be common, histology‐agnostic biologic or molecular mechanism(s).…”
Section: Criteria For and Predictors Of Hpd According To Different Rementioning
confidence: 99%
“…Another key question in HPD is whether there are clinical or molecular features that are associated with an increased risk of accelerated growth after checkpoint blockade. Predictors of HPD have included age ≥ 65 years, female gender, regional recurrence of disease, having more than two sites of metastases, low baseline highly differentiated CD4+ T cells or effector memory CD8+ T cells, high severely exhausted T cells or proliferating T regulatory cells, clustered CD163 + PD‐L1 + CD33 + macrophages with epithelioid morphology, and genomic markers (mainly MDM2 / MDM4 alterations and EGFR alterations; Table ) . There are inconsistencies between studies in that some have not shown age or sex to be predictors.…”
Section: Criteria For and Predictors Of Hpd According To Different Rementioning
confidence: 99%
See 1 more Smart Citation
“…Hyperprogressive disease refers to a remarkably accelerated tumor growth rate (TGR) that leads to poor prognosis in patients under ICB therapy particularly anti‐PD‐1/PD‐L1 agents . Currently, no consensus has been reached on the definition of HPD .…”
Section: The Role Of Medical Imaging In Immunotherapy: Response Assesmentioning
confidence: 99%
“…For instance, Champiat et al first reported HPD as a RECIST 1.1 progression before ICB therapy and a twofold or greater increase in TGR during immunotherapy, whereas Ferrar et al defined HPD as a disease progression at the first evaluation with at least an increase of 50% ΔTGR (the variation of TGR before and on treatment) (Figure ) . The incidence of HPD was reported to range from 7% to 29% across different types of carcinoma . However, the discordance in the definition of HPD across published literatures challenges the direct comparison of data.…”
Section: The Role Of Medical Imaging In Immunotherapy: Response Assesmentioning
confidence: 99%